2015
DOI: 10.1371/journal.pone.0117340
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Detectable Allergenicity in Genetically Modified Maize Containing “Cry” Proteins as Compared to Native Maize Based on In Silico & In Vitro Analysis

Abstract: BackgroundGenetically modified, (GM) crops with potential allergens must be evaluated for safety and endogenous IgE binding pattern compared to native variety, prior to market release.ObjectiveTo compare endogenous IgE binding proteins of three GM maize seeds containing Cry 1Ab,1Ac,1C transgenic proteins with non GM maize.MethodsAn integrated approach of in silico & in vitro methods was employed. Cry proteins were tested for presence of allergen sequence by FASTA in allergen databases. Biochemical assays for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Our findings are in accordance with the earlier study by Mathur et al [1] on the safety assessment of Cry1Ab, Cry1Ac and Cry1C proteins using in silico tools, where they predicted them as safe for incorporation in GM Maize.…”
Section: Bioinformatics Analysissupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in accordance with the earlier study by Mathur et al [1] on the safety assessment of Cry1Ab, Cry1Ac and Cry1C proteins using in silico tools, where they predicted them as safe for incorporation in GM Maize.…”
Section: Bioinformatics Analysissupporting
confidence: 93%
“…In the present study, the in silico analysis of Cry1Ab protein used in the transgenic potato indicated no evidence for any similarity between Cry1Ab and any known toxic or allergenic proteins. Thus, our findings confirm the findings of earlier workers [1,8,19]. Moreover, the bioinformatic analysis of NPTII protein in transgenic potato plants showed no significant alignment and homology at the domain level with proteins known to be toxic or bioactive.…”
Section: Bioinformatics Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…The SGF and SIF models provide allergenic potential evaluation methods, since food proteins are rapidly digested by gastric and intestinal processes [3,43]. The combined results of CBB-stained SDS-PAGE gels and Western blotting showed that transgenic sugarcane protein, at time zero as a control sample, underwent no significant degradation changes in the absence of pepsin and trypsin (Figure 2A,B, upper and middle).…”
Section: In Vitro Simulated Gastric Fluids (Sgf) and Simulated Intestmentioning
confidence: 99%